Internet commerce and policy in Singapore: towards building a technopolis. - Lee, Lora Si Si. (2008)
Eighteen industry stakeholders and ten representatives from various industry organizations participated in this study aimed at identifying the Singapore government's and private sector's roles incorporating technology, capital and people as well as harnessing innovation, entrepreurship, the flow of ideas in the development of a technopolis.